ANALISIS PENGARUH INFLASI TERHADAP LAJU PERTUMBUHAN EKONOMI DI KOTA JAMBI - Agus Topo Subekti (Jurnal Khazanah Intelektual, 2023)
Economic growth in Jambi City is a development of activities in the economy which causes the goods produced in society to increase. A high inflation rate will have a negative impact on economic growth, a high inflation rate will reduce economic growth. In this study examines the effect of inflation on economic growth in the city of Jambi. The purpose of this study is to determine the effect of inflation on economic growth in Jambi City so that it is expected to assist the government in determining policies related to inflation and economic growth. The type of research in this study is associative explanatory research, namely research used to analyze variables and their influence between one variable and another. This study uses a simple regression analysis method. The result of this study is that inflation has a negative and significant effect on economic growth in Jambi City. If inflation rises, economic growth will decrease and vice versa if inflation falls, economic growth will increase.